Inzidenz, Behandlung und Prognose des Prostatakarzinoms in Baden-Württemberg: Analyse anhand von Krebsregisterdaten - Worst, Thomas; Surovtsova, Irina; Vogel, Tilo; Zauser, Martin; Neuberger, Manuel; Wessels, Frederik; Michel, Maurice Stephan; Nuhn, Philipp; Morakis, Philipp (Die Urologie, 2024)
Background Prostate cancer (PCa) is the most common solid tumor in men in Germany. Collection of epidemiological and clinical data has been centralized for several years due to legal requirements via the state cancer registries. Thus, the reporting of diagnosis, therapy, and progression of cancer is obligatory in Germany. These data needs to be processed based on the questions of the treating physicians. Objectives Intention of this work was to present the development of new cases, disease stages, treatment procedures and prognosis of PCa in Baden-Württemberg (BW). Methods For this purpose, data of the cancer registry BW regarding patients with PCa first diagnosed between 2013 and 2021 were evaluated. The evaluation was performed using descriptive statistics, Χ2 test and Kaplan-Meier analysis. Results A total of 84,347 new diagnoses of PCa were reported. Clinical stage was present in 55.3% of patients. Assignment by International Society of Urological Pathology (ISUP) groups was present in 75.7%. A steady increase in primary diagnosis was evident through 2019. The proportion of primary metastatic disease decreased (2013: 19.6% vs. 2021: 12.0%), and the proportion of localized tumors increased (2013: 65.5% vs. 2021: 77.1%). Radical prostatectomy (RP) dominated the treatment of localized tumors with a mean of 60.1%. The proportion of robot-assisted surgery increased from 23.7% (2013) to 60.8% (2021) with a decrease in the R1 rate from 34.8 to 26.2%. Progression-free survival correlated closely with tumor stage and ISUP group. Conclusion An increase in PCa cases and a decrease of advanced tumors were observed. Treatment was mostly surgical in localized stages, with increasing proportion of robotic-assisted RP. Early diagnosis and treatment are critical for long-term prognosis.
Online veröffentlicht: 5. Februar 2024
Gesehen am 03.02.2025